2017
DOI: 10.31018/jans.v9i2.1274
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on performance and variability in different sweet orange (Citrus sinensis Obseck) cultivars under Punjab conditions

Abstract: Based on morphological characterization, the performance of eighteen sweet orange, (Citrus sinensis Obseck) cultivars were evaluated. On the basis of two year data, the maximum mean fruit weight (316.25 gm) was recorded in Moro, while the maximum mean fruit diameter and mean fruit length was recorded in Mosambi and Olinda Valencia (87.32 mm and 81.33 mm, respectively). Albedo thickness was recorded maximum in Ruby Nucellar (3.42 mm). Highest total soluble solids was recorded in cultivar Moro (11.45 0 brix), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
1
1
3
Order By: Relevance
“…The highest TSS (10.21%) was recorded from the genotype BAU Malta-1 which is statistically at par with BARI Malta-1 (9.20%) and the lowest (6.84%) was in variegated Malta. This was coherent with earlier reports by Baswal et al, (2017), who found the same range of TSS among different sweet orange genotypes in Punjab.…”
Section: Chemical Properties Of Eight Selected Sweet Orange Genotypessupporting
confidence: 93%
See 1 more Smart Citation
“…The highest TSS (10.21%) was recorded from the genotype BAU Malta-1 which is statistically at par with BARI Malta-1 (9.20%) and the lowest (6.84%) was in variegated Malta. This was coherent with earlier reports by Baswal et al, (2017), who found the same range of TSS among different sweet orange genotypes in Punjab.…”
Section: Chemical Properties Of Eight Selected Sweet Orange Genotypessupporting
confidence: 93%
“…The number of segments varied from 18 in variegated Malta to 28 in BAU Malta-3. However, the range of segments in this study was higher than the recorded segments (Baswal et al, 2017), possibly due to the difference in the genotype, climate and geography.…”
Section: Physical Characteristics Of Eight Selected Sweet Orange Genotypescontrasting
confidence: 65%
“…La fisiología del polen, especialmente la germinación y la viabilidad, ha recibido una atención considerable para aplicarse, tanto en programas de mejoramiento de plantas, como en la conservación, adaptación y comprensión del comportamiento fisiológico de la fertilización de los granos de polen (Khan y Perveen, 2014). La caracterización y la viabilidad de los granos de polen son herramientas útiles para guiar los cruzamientos en programas de mejoramiento (Soares et al, 2013), ya que permite discriminar y usar solo los mejores donadores de polen y hacer un buen manejo de este en los trabajos de polinización (Gaaliche et al, 2013;Baswal et al, 2015).…”
Section: Introductionunclassified
“…La viabilidad del polen y su poder germinativo en laboratorio se puede determinar mediante a): Pruebas de germinación in vitro (Moura et al, 2015;Shekari et al, 2016); b) medición de la actividad enzimática (Gozlekci et al, 2011;Soares et al, 2013;Demir et al, 2015); y c) la tinción del citoplasma del grano de polen (Maiti y Rodríguez, 2015;Baswal et al, 2015). Sin embargo, Soares et al (2013); Kundu et al (2014); Shekari et al (2016), coinciden que la germinación in vitro es más confiable ya que los métodos de tinción pueden sobreestimar la viabilidad del polen.…”
Section: Introductionunclassified
See 1 more Smart Citation